Investigating Knocking Potential, Cycle Stability, and Emission Characteristics in Lean Spark Ignition Engine with Gasoline, Ethanol, and Methanol - Mokhtar Mokhtar; Bambang Sugiarto; Askar Adika Agama; Ade Kurniawan; Ahmad Syihan Auzani (Automotive Experiences, 2024)
In this paper, an investigation of the use of gasoline-ethanol-methanol on the spark ignition engine is presented, it is not common practice on public roads to use three fuels simultaneously in a spark-ignition engine. Using methanol reduces the ignition delay during combustion, especially at lean air-fuel ratios, and reduces knocking potential in small amounts. The best result ignition delay with value Î»= 1,3 obtained in the E5M15 mixture with SoC occurred at 325 CAo, while the value Î»= 1,0 also obtained on the same mixture with SoC occurred at 321,5 CAo. The CCV results indicate a more sloping increase in the COV (coefficient of variation) value when using GEM fuel, particularly with the addition of more methanol. The addition of methanol enhances combustion progression and improves the ability of the fuel blend to sustain combustion under lean conditions. Regarding the torque and power values, at Î»= 1,0; 1,1; 1,2 are not significantly different, while the value Î»= 1,3 is below the other Î» values.